Basal cell carcinoma of the vulva: a case report and systematic review of the literature. (2nd December 2018) - Renati, Sruthi; Henderson, Christopher; Aluko, Ashley; Burgin, Susan
Abstract: The vulva is an unusual site for basal cell carcinoma (BCC). Vulvar BCC accounts for <1% of all BCCs and <5% of all vulvar malignancies. We report the case of an 83 year‐old woman who presented with a 2‐month history of a tender labial growth, with histopathology confirming nodular BCC. We conducted a systematic literature review of the characteristics of reported cases of vulvar BCCs. A comprehensive systematic review of articles indexed for MEDLINE and Embase yielded 96 reports describing 437 patients with 446 BCCs of the vulva. The mean age at presentation was 70 (range 20–100). Most women had no underlying vulvar disease. Approximately 60% of cases were of the nodular subtype. Treatment approach varied widely with over half of cases treated with wide local or local excision. Mohs micrographic surgery (MMS) for vulvar BCC was first reported in 1988 with seven total MMS cases reported. Twenty‐three cases of recurrence have been reported; 21 of these cases after local excision but none following MMS. Vulvar BCC is a rarely reported cancer that affects older women predominantly. MMS represents a promising treatment for BCC in this anatomic location.